1997
DOI: 10.1021/bi963126a
|View full text |Cite
|
Sign up to set email alerts
|

DNA Binding Specificity of MunI Restriction Endonuclease Is Controlled by pH and Calcium Ions:  Involvement of Active Site Carboxylate Residues

Abstract: Gel shift analysis reveals [Lagunavicius, A., & Siksnys, V. (1997) Biochemistry 36 (preceding paper in this issue)] that at pH 8.3 in the absence of Mg2+, MunI restriction endonuclease exhibits little DNA binding specificity, as compared with the D83A and E98A mutants of MunI. This suggests that charged carboxylate residue(s) influence the DNA binding specificity of MunI. In our efforts to establish the determinants of MunI binding specificity, we investigated the possible role of the ionic milieu, and we foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 32 publications
6
55
1
Order By: Relevance
“…Thus either lowering the pH or adding divalent metal ions has a large effect on T5FEN-substrate interactions, but these effects are not additive. Similar stimulation of binding of DNA substrates at lowered pH or by Ca 2ϩ ions has been observed with other metallonucleases and been assigned to protonation or binding of Ca 2ϩ ions at the active site carboxylates (28). Here the protonation state of DNA-binding residues could also be a factor (29,30).…”
Section: The Effect Of Divalent Metal Ions On Wt Fen-substratesupporting
confidence: 65%
“…Thus either lowering the pH or adding divalent metal ions has a large effect on T5FEN-substrate interactions, but these effects are not additive. Similar stimulation of binding of DNA substrates at lowered pH or by Ca 2ϩ ions has been observed with other metallonucleases and been assigned to protonation or binding of Ca 2ϩ ions at the active site carboxylates (28). Here the protonation state of DNA-binding residues could also be a factor (29,30).…”
Section: The Effect Of Divalent Metal Ions On Wt Fen-substratesupporting
confidence: 65%
“…8A). Most likely, this band represents a complex, in which one Mva1269I molecule is bound specifically to the target and another one is bound nonspecifically to the same DNA molecule, as observed with some other REases (38). DNA binding studies of the nicking mutants D537A and E554A/ K556A revealed that they form specific DNA complexes at concentrations comparable to those of the wt enzyme (Fig.…”
Section: Mva1269i Restriction-modification System Consists Of Two Genes-mentioning
confidence: 52%
“…Previous mutational studies of the active site residues of restriction enzymes, e.g. EcoRI [24], MunI [25] and BamHI [26], revealed that Ala replacements do not interfere with DNA binding or even enhance binding a⁄nity in comparison to the wt enzymes. Thus, observed DNA binding and cleavage phenotypes of K182A and E195A mutants are in principle consistent with a proposed active site function of K182 and E195 residues in Ecl18kI.…”
Section: Discussionmentioning
confidence: 99%